May the Other Side Also be Heard? Some Remarks Regarding the Chances for a Response to Opinion 2/13 From the ECtHR on the Awakening of the EU Accession to the ECHR Process - Jóźwicki, Władysław (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2020)
This paper takes up a question whether there exists a possibility for the European Court of Human Rights (ECtHR) to take a stand on the (in)famous Opinion 2/13 by the Court of Justice of the European Union (CJEU), and to address contained in it argumentation from the perspective of the Strasbourg system's conditions for accession. Particularly, it will focus on the question whether the Convention system provides for an appropriate procedure. The paper will not engage into a discussion on how the contentious issues should be addressed by the ECtHR, but will focus on answering whether it at all may have a chance to address them in the current legal setting through advisory procedures with which the European Convention on Human Rights (ECHR) system is equipped. The text will argue that even if both the Articles 47-49 of the Convention advisory procedure as well as the Protocol 16 to the Convention advisory procedure for the sake of their function and scope could not be applied to directly, holistically and systematically tackle Opinion 2/13, then at least the latter could provide a forum to do that in a limited scope and in an indirect way. While the mechanism has been designed with a completely different purpose, some of the features of the Protocol 16 advisory procedure may even seem to incite such a use, especially in the context of the increasingly turbulent relations between the CJEU and the European Union (EU) Member States’ highest courts and tribunals in the field of fundamental rights.